Non-Linear Dependence in ASEAN-5 Foreign Exchange Rates: An Insight from a Battery of Non-Linearity Tests - Lim, Kian Ping (2001)
The main purpose of this study is to provide a deeper insight into the non-linear generating mechanism in the ASEAN-5 exchange rate returns series. To achieve that end, the differing power of the non-linear tests against certain alternatives is utilized. Specifically, the BDS and Hinich bispectrum tests are employed which provide valuable information on the adequacy of the current framework of ARCH-type models in capturing the non-linear dynamics in ASEAN-5 currencies. Daily data is used in this study covering the period from 1 990 to March 200 1 . The five ASEAN countries selected are Malaysia, Singapore, Thailand, Indonesia and the Philippines. The results from the BDS test indicate strong evidences of non-linearity in the ASEAN-5 exchange rate series. However, this conveys little information on the nature of the detected non-linearity since the BDS test has high power against vast class of alternatives. Further application of the Hinich bispectrum test can provide valuable non-linear identification information, in which the results reveal strong evidences against the adequacy of the ARCH-type models in explaining the nonlinear dynamics in ASEAN-5 exchange rate series. The evidences of non-linearity in ASEAN-5 currencies have profound implications on the validity of weak-form market efficient hypothesis, model adequacy as well as the pricing of future derivatives. Furthermore, the results might prompt economists or policy makers to consider alternative policy advice based on models characterised by non-linear dynamics.